Advances in polymer science = Fortschritte der Hochpolymeren-Forschung. Volume 12 - Cantow, H. J. (Springer-Verlag, 1973)
Viscoelastic properties of dilute polymer solutions / Osaki, K. ; The mechanism of olefin polymerization by Ziegler-Natta catalysts / W. L. Carrick ; Applications of infrared spectroscopy to ethylene-propylene copolymers / Tosi, C., Ciampelli, F. ; ESR study od photodegradation of polymers / Tsuji, K.
Keywords: polymery; polymerizace; polyolefiny; infračervená spektroskopie; viskoelasticita; roztoky; polymers; polymerization; polyolefins; infrared spectroscopy; viscoelasticity; solutions; sborníky; miscellanea